Facile Synthesis of 9-Acetyl-pyrano[2,3-F]isoflavones - Chenna Krishna Reddy, R.; Madhusudana Rao, G.; Thirupal Reddy, M.; Rami Reddy, Y.V. (Asian Journal of Chemistry, 2013)
The Baylis-Hillman reaction of 7-hydroxy-8-formyl isoflavones (1a-f) react with methyl ketone in presence of l,4-diazobicyclo[2.2.2]octane with nitrogen atmosphere to give 9-acetyl-pyrano[ 2,3-f]isoflavones (3a-f) in good yields.